2017
DOI: 10.1038/cddis.2017.471
|View full text |Cite
|
Sign up to set email alerts
|

Berberine induces oxidative DNA damage and impairs homologous recombination repair in ovarian cancer cells to confer increased sensitivity to PARP inhibition

Abstract: Many cancer drugs exert their therapeutic effect by inducing oxidative stress in the cancer cells. Oxidative stress compromises cell survival by inflicting lesions in macromolecules like DNA. Cancer cells rely on enhanced antioxidant metabolism and increased DNA repair function to survive oxidative assault. PARP1, a protein that senses DNA-strand breaks and orchestrates their repair, has an important role in the repair of oxidative DNA damage. Berberine, an alkaloid compound present in many herbal plants, is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 28 publications
5
37
0
Order By: Relevance
“…In addition, berberine modulated the sensitivity of cisplatin through the miR-93/PTEN/AKT signaling pathway in ovarian cancer cells (32) and attenuated the antitumor activity of 5-FU, camptothecin and paclitaxel (33). Berberine was also found to sensitize cancer cells to PARP and epidermal growth factor receptor inhibitors (18,34). In the present study, berberine and sorafenib were found to exert anti-proliferative effects on HCC cells in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, berberine modulated the sensitivity of cisplatin through the miR-93/PTEN/AKT signaling pathway in ovarian cancer cells (32) and attenuated the antitumor activity of 5-FU, camptothecin and paclitaxel (33). Berberine was also found to sensitize cancer cells to PARP and epidermal growth factor receptor inhibitors (18,34). In the present study, berberine and sorafenib were found to exert anti-proliferative effects on HCC cells in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 52%
“…(Berberidaceae) has long been a part of traditional Chinese and Ayurvedic medicine. Preclinical efficacy of berberine has been established in various cancers including colon , breast (Zhao et al, 2017), gastrointestinal (Hesari et al, 2018), oral , liver (Tsang et al, 2015), pancreas (Abrams et al, 2019), prostate (Youn et al, 2018), ovarian (Hou et al, 2017), and cervical (Mahata et al, 2011) cancers. Despite large preclinical efficacy data, clinical trials related to the evaluation of true potential of berberine as an anticancer agent are limited.…”
Section: Phytochemicals Evaluated In Clinical Trialsmentioning
confidence: 99%
“…Studies have demonstrated that cellular senescence is a natural barrier in the development of human cancer . Induction of senescent‐like growth arrest has become a new strategy for anticancer treatment . Thus, these results have important implications for matrine in the treatment of GBM, particularly due to the fact that aberrant signaling of PI3K/AKT occurs in GBM through the frequent loss of the tumor suppressor gene PTEN .…”
Section: Discussionmentioning
confidence: 99%